Hypernatremic dehydration in newborns - NC, Shivaprakash; Ahmed, Touseef (International Journal of Contemporary Pediatrics, 2017)
Hypernatremic dehydration is an uncommon problem in newborns. Infants who fail to breast-feed may develop hypernatremic dehydration, a condition that can be fatal or cause major morbidity. Early discharge, lack of timely follow-up, or poor information during pregnancy or after delivery play important roles. Hypernatremic dehydration can lead to neonatal morbidity and mortality. We are reporting two cases of exclusively breastfed neonates with hypernatremic dehydration.